Adherence to HIV post-exposure prophylaxis: A multivariate regression analysis of a 5 years prospective cohort. Issue 1 (January 2018) - Malinverni, Stefano; Libois, Agnès; Schuster, Monica; De Wit, Stéphane; Mols, Pierre; Gennotte, Anne-Françoise
Highlights: Increased treatment adherence to nPEP is associated with being MSM, having a health insurance, having had a previous nPEP treatment and with an older age. Reduced treatment adherence to nPEP is associated with sexual assault survivors and foreign patients. Sexual assault survivors are overexposed to the deleterious effect on compliance of not having a health insurance. Daytime consultations for nPEP are associated with increased treatment adherence when compared to nighttime consultations. Summary: Background: Non-occupational post-exposure prophylaxis (nPEP) is a recommended public health intervention after a sexual or percutaneous exposure to human immunodeficiency virus (HIV). Methods: We conducted a prospective observational study recording consultations for nPEP at a reference HIV center in Brussels, Belgium from January 2011 to December 2015. We recorded attendance to follow-up, reported completion of nPEP and pharmacy records to measure adherence. Multivariate logistic regressions were performed to identify independent risk factors for adherence to nPEP and attendance to first follow-up visit at the STI clinic. Findings: Among 1881 patients receiving nPEP, 66.4% had a documented completion of a 28-day course of nPEP and 87.3% attended their first follow-up clinic visit. MSM (OR, 1.40; 95%CI, 1.04–1.90), being a native Belgian (OR, 1.50; 95%CI, 1.18–1.90), older age (OR, 1.02; 95%CI, 1.01–1.04), being a sexual assault survivor (OR, 0.59; 95%CI, 0.38–0.91), having had a previous nPEP treatment (OR, 1.44; 95%CI, 1.02–2.02), consultation during daytime (OR, 1.35; 95%CI, 1.07–1.70) and benefitting from a health insurance (OR, 2.11; 95%CI, 1.58–2.89) were significant independent predictors for adherence to nPEP. Patients whose initial treatment was AZT/3TC/IDV/r had similar adherence than patients on d4T/3TC/LPV/r (OR, 0.898; 95%CI, 0.68–1.20). Interpretation: Multiple independent risk factors for nPEP retention into care and adherence are present at treatment initiation and might be targeted by tailored interventions. Sexual assault victims are overexposed to deleterious consequences of the lack of health insurance on compliance.